Effect of Water Potential and Void Ratio on Erodibility for Agricultural Soils. Issue 3 (16th June 2017) - Liu, Q.J.; Wells, R.R.; Dabney, S.M.; He, J.J.
Abstract : Core Ideas: Critical shear stress can be modeled by silt content, void ratio and water potential. Erodibility can be predicted by critical shear stress, clay content and void ratio. Bulk density displayed a convex trend as antecedent soil moisture increasing. Soil erodibility has confounded researchers for decades. Difficulties arise with initiation of motion, pore‐water status, physical, and perhaps biological, material properties and type of applied energy (i.e., rainfall, runoff, freezing or thawing, wind). Though specific tests have been developed to determine critical shear stress and soil erodibility, solutions do not seem to conform to theory. We have models for erosion assessment and, although each provides practical information for planning and management, all share a need to improve predictions for soil detachment. Here, a series of submerged jet tests (JET) are performed on samples of three soils prepared to represent agricultural conditions (i.e., modest bulk density), five initial soil water contents are imposed during sample packing that affected soil void ratio, and four water potential gradients are imposed during jet testing. Results, for both coarse‐ and fine‐grained soils, indicate that critical shear stress can be predicted with knowledge of the silt content, void ratio and water potential gradient, and soil erodibility can be predicted with knowledge of critical shear stress, clay content and void ratio. This study was limited by the number of soils examined; however, the results are thought provoking.